Using a novel shear apparatus coupled with acoustic emission to investigate shear fracture evolution of cement-based materials in macro- and micro-views. (30th October 2018) - Chen, Wei-Chih; Chen, Li-Hsien; Chen, Yao-Chung
Highlights: A novel shear apparatus with an opened-shear-box was designed. Shear fracture initiation and propagation of cement mortar was observed. The angular-shape aggregate has higher stiffness than rounded-shape aggregate. The crack initiation occurred near the center part of the specimen. The distribution of AE events before the peak consists with that of macro-crack. Abstract: It is difficult to investigate the shear fracture triggering position and subsequent fracture propagation using traditional direct shear testing due to its closed-shear-box design. To examine the fracture evolution of cement-based materials subjected to shear stresses, a novel shear apparatus with an opened-shear-box and crack displacement control coupled with a non-destructive technique of acoustic emission (AE) was developed in this study. The complete loading curve in the macro-view and corresponding AE event (micro-crack) development were then obtained. The fracture behaviors affected by the shear angle and the aggregate shape of cement mortar were also investigated. The test results showed that the stiffness and peak shear stress decreased with an increase in the shear angle. The stiffness of the specimen with angular-shaped aggregate was higher than that of the specimen with rounded-shaped aggregate. The localization of AE events occurred before the peak and were located near the middle of the specimen. The position of the AE localization was related to that of the macro-crack initiation. After localization, the AE events then propagated following the shear direction. A comparison of the distribution of AE events before the peak with the position of the macro-crack showed good agreement. The results obtained in this study provide a better understanding of the shear fracture mechanism of cement-based material.